THE EFFECT OF CAPITAL STRUCTURE ON FIRM VALUE WITH PROFITABILITY AS VARIABLE MEDIATOR IN INDUSTRIAL COMPANIES LISTED ON THE IDX - Theresya Evelyne; Elsa Imelda; Natasya Cindy Hidajat (Graduate Program of Universitas Tarumanagara, 2024)
This research discusses the influence of capital structure on firm value which is mediated by profitability in industrial companies listed on the Indonesia Stock Exchange from 2020 to 2021. These variables include capital structure (as measured by debt to equity ratio [DER]), profitability (as measured by return on equity [ROE]), and firm value (as measured by price to book value [PBV]), Based on the purposive sampling strategy, 96 data from 32 companies were chosen as research samples. Verification analysis is used in this study, with data analysis techniques through conditional process analysis and used SPSS Process Macro Model 4 was used to process the data. The study showed that: capital structure affects profitability, Capital structure affects firm value, Profitability affects firm value, and Profitability mediates the effect of Capital Structure on Firm Value.